Scheduled castes and their status in India - "Khan,Mumtaz Ali" (New Delhi)
THE MAIN OBJECT of the study was to assess the changes, if any, which have taken place in several aspects of the life of the Scheduled Castes who were subject to several forms of disabilities in the past. The study also aims at evaluation of the working of the governmental policies and programmes for the upliftment of the Scheduled Castes since Independence.
Keywords: Scheduled castes